A review of environmental enrichment as treatment for problem behavior maintained by automatic reinforcement. Issue 1 (21st September 2018) - Gover, Holly C.; Fahmie, Tara A.; McKeown, Ciobha A.
Abstract : We reviewed studies that used environmental enrichment as treatment for problem behavior maintained by automatic reinforcement. A search of behavior analytic journals produced 71 publications with a total of 265 applications of environmental enrichment used alone or in conjunction with alternative behavior manipulations (e.g., prompting, reinforcement) and problem behavior manipulations (e.g., blocking, restraint). Environmental enrichment, as a sole intervention, was efficacious in 41% of the sample. Alternative behavior manipulations, problem behavior manipulations, and a combination of both improved the overall efficacy of environmental enrichment. We discuss factors that may influence the efficacy of environmental enrichment, current trends in research on this topic, and implications for both practitioners and researchers.